Converged voice access to data (CVAD) - Talevski, Alex; Chang, Elizabeth; Dillon, Tharam S. (IEEE, 2007)
The rapid growth of the Internet and widespread use of mobile computing and telephony has resulted in a broad range of ways to communicate and access information. Data and telecommunications convergence promises a wide range of possible solutions that will increase productivity, reduce costs, and provide new opportunities and revenues for enterprises. However, such converged telecommunications and data services have been largely isolated to static environments where fixed Personal Computers (PC) and an Internet connection are used in conjunction with various software tools to simulate a pseudo converged session. Generally, data presented on the internet and in enterprise applications is not available on voice networks and vice-versa. Due to the versatile nature of today's enterprise, a feature-rich, flexible, adaptive and widely accessible convergence solution is required. This paper presents an Interactive Voice Response (IVR) driven approach that uses Converged Voice Access to Data (CVAD) services. The CVAD solution offers enhanced service effectiveness, flexibility and convenience for professionals on the move.